2021
DOI: 10.1111/ejn.15455
|View full text |Cite
|
Sign up to set email alerts
|

Background white noise and speech facilitate visual working memory

Abstract: In contrast to background white noise, the detrimental effects of background speech on verbal working memory (WM) were often explained by speech interference in the same verbal modality. Yet, those results were confounded with potential differences between arousal levels induced by speech and white noise. To address the role of arousal, in the present study, we minimized the verbal interference by using a visual WM task to test the influence of background speech or white noise. Electrodermal activity (EDA) was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Second, the auditory white noise (presented at 70 dB) might be intrinsically arousing, irrespective of the inability of subjects to predict when the sound will be presented. Consistent with this idea, continuously presented background auditory white noise also affects human task performance (Corcoran, 1962;Han et al, 2021;Söderlund et al, 2010). Future research should investigate if the bias-suppressing effect of the accessory stimulus also occurs during more frequent accessory stimuli, for example on 25% of 50% of trials (Lippert et al, 2007;Tona et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…Second, the auditory white noise (presented at 70 dB) might be intrinsically arousing, irrespective of the inability of subjects to predict when the sound will be presented. Consistent with this idea, continuously presented background auditory white noise also affects human task performance (Corcoran, 1962;Han et al, 2021;Söderlund et al, 2010). Future research should investigate if the bias-suppressing effect of the accessory stimulus also occurs during more frequent accessory stimuli, for example on 25% of 50% of trials (Lippert et al, 2007;Tona et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…In terms of memory, a study on monkeys indicates that white noise in delayed response testing improves working memory [7]. A recent study also shows that white noise benefits working memory performance, helping to reduce the participants' guess rate of tasks [8]. However, Herweg and Bunzeck reported that the accuracy and reaction time of the working memory task were not influenced by white noise played during the memory encoding and maintenance period, while the noise played during the delay period impaired working memory [9].…”
Section: Introductionmentioning
confidence: 99%